Macroeconomics : theories, policies, and international applications - Miller, Roger LeRoy. (South-Western College/Thomson Learning, 2001)
The macroeconomy. Measuring macroeconomic variables. Classical macroeconomic theory. The theory of economic growth. Essentials of the Keynesian system. Money in the traditional Keynesian system. Fiscal policy in the traditional Keynesian system. The Keynesian and monetarist views on price and output determination...